Evidence-based medicine in pre-clinical years: a study of early introduction and usefulness - YOGESH ACHARYA; M.V. RAGHAVENDRA RAO; SATEESH ARJA (Journal of Advances in Medical Education and Professionalism, 2017)
Introduction: Evidence Based Medicine (EBM) has established itself as a strong predictor of future medical practice by medical students. The purpose of this study was to determine the effectiveness of EBM in pre-clinical years and reflect on selfassessment skill of 4th semester medical students regarding the understanding of EBM and its various determinants. Methods: All of the 4th semester (MD4) medical students at the Avalon University of Medical School, Curacao who had completed their EBM curriculum were asked to voluntarily participate in a cross sectional student survey containing qualitative and quantitative questionnaires in a 10-point scale. The students’ responses were analyzed statistically and the results reported. Results: Twenty-three students participated in the survey. 91% of them reported that EBM had helped them to better understand research process and 95% believed that EBM was necessary to develop clinical skills in the future. 78% of the students agreed that they were provided with enough resources for effective implementation of EBM in the university. All participants (100%) self reported that they could appraise the research articles effectively (mean score 8.26, S.D-1.45). Conclusions: EBM is an integrative and comprehensive way to successfully adopt concepts of acquired medical knowledge for effective medical practice. Early introduction of EBM in preclinical years proved favorable in students and better equipped them with the ability to critically apprehend and appraise new research and innovations in medicine for optimal learning experience. There is a definitive need for scientific and systematic design of the curriculum for early introduction of EBM in pre-clinical years, best suited for the students. The principles should be directed towards further research for the effective implementation of EBM to enhance clinical skills.